Refining core competencies of first-line nurse managers in the hospital context: A qualitative study - Joko Gunawan; Yupin Aungsuroch; Mary L. Fisher; Colleen Marzilli; Nazliansyah; Ety Hastuti (Elsevier, 2023)
Objectives: As the world moves towards a new normal, challenges continue to emerge while simultaneously inspiring us with new solutions. Strengthening the skills of first-line nurse managers (FLNMs) to fulfill a wide range of complex roles and responsibilities effectively necessitates refining core competency guidelines or standards. This study aimed to explore the perceived core competencies of Indonesian FLNMs within the context of the post-pandemic era. Methods: The study employed a qualitative descriptive design. Face-to-face interviews were conducted in a public hospital in Indonesia from January 2022 through August 2022. Seven head nurses with direct experience managing a unit during the COVID-19 pandemic were selected. The interviews were audio-recorded, transcribed verbatim, and validated by re-listening. Data were analyzed using thematic analysis. Results: Four main themes of the core competencies developed, including 1) managerial core competencies, 2) clinical core competencies, 3) technological core competencies, and 4) socio-emotional skills/personal traits consisting of the following: be brave, fast, patient, optimistic, consistent, and responsible. Conclusions: The findings demonstrate that the managerial and clinical core competencies of the FLNMs must be aligned, while technological core competencies are the mediating component of both. Personal traits are essential for FLNMs as they undergird the other three core competencies and the success of the FLNMs.